PEMANFAATAN LIMBAH TONGKOL JAGUNG SEBAGAI PAKAN DAN KOMPOS DI DESA MUSTIKA KABUPATEN BOALEMO - Sutianto Pratama Suherman; Arafik Lamadi; Shindy Hamidah Manteu (Jurnal Abdi Insani, 2023)
Mustika Village is a village located in Paguyaman District, Boalemo Regency, Gorontalo Province. In facing the Asian Economic Community (AEC), each region must do more to improve its local economy, one way is to maximize its potential. One of the leading commodities and has the potential to be developed in Mustika village is corn which has agricultural waste that has not been utilized properly. The purpose of this activity is to empower the community in the process of utilizing corn cobs as a raw material for feed, in an effort to increase the selling value of underutilized corn cobs. The method used consists of three stages, namely the first stage of surveys and interviews; both socialization and material counseling; and third, training on corn cob waste processing. The results of this activity, starting with observations and interviews, data collection of farmer groups, preparation of activities according to the results of field observations, conducting counseling to provide new insights and information to the community; conduct training in improving community skills, as well as direct practical assistance to the community or farmer groups. The conclusion with this program is that the community, especially farmer groups, are able to process corncob waste into feed and compost in community development.